-11-5r=-8(5r-3)

Simple and best practice solution for -11-5r=-8(5r-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11-5r=-8(5r-3) equation:


Simplifying
-11 + -5r = -8(5r + -3)

Reorder the terms:
-11 + -5r = -8(-3 + 5r)
-11 + -5r = (-3 * -8 + 5r * -8)
-11 + -5r = (24 + -40r)

Solving
-11 + -5r = 24 + -40r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '40r' to each side of the equation.
-11 + -5r + 40r = 24 + -40r + 40r

Combine like terms: -5r + 40r = 35r
-11 + 35r = 24 + -40r + 40r

Combine like terms: -40r + 40r = 0
-11 + 35r = 24 + 0
-11 + 35r = 24

Add '11' to each side of the equation.
-11 + 11 + 35r = 24 + 11

Combine like terms: -11 + 11 = 0
0 + 35r = 24 + 11
35r = 24 + 11

Combine like terms: 24 + 11 = 35
35r = 35

Divide each side by '35'.
r = 1

Simplifying
r = 1

See similar equations:

| 31e=102 | | 5x^2+40=30x | | -18=16 | | -11=-45r-3 | | 63x=8p-14 | | 6x-6-3x=x+5+x | | 9a+2b+8a+3b= | | 19z=38 | | 19z=28 | | 5x^2-33x+56=0 | | 7.5+n=9.63 | | 2d-6d=5 | | (1-3x)=4 | | 4(3x+1)+8x=-23-7x | | 7.95-3.86=n | | 8=-5+z | | 7.95+3.86=n | | 6x+8=25-2 | | 5x+8=25-1 | | 2x^3=256 | | -22=2b | | 5x+9=25-2 | | 3x-6+15=41 | | 245-x^2=0 | | 5x+8=25-2 | | 2y+4x+74=180 | | 1-5v=-14 | | (10x-7)(3x+1)=0 | | 25+t=-132 | | 5(2x)(x)+152= | | 55.4=v-(-69.1) | | -2=t+20 |

Equations solver categories